Aging and Driving: A Comparison of Driving Performance Between Older and Younger Drivers in an On-Road Driving Test - Rolf Robertsen (SAGE Open, 2022)
It is important to examine changes in driving performance and driver behavior with increasing age to improve road safety. The main purpose of this study was to explore if there were any differences in a group of young drivers ( n  = 36, M age  = 32) and a group of elderly drivers ( n  = 40, M age  = 72) on driving performance and driving skills on a number of driving tasks. An on-road driving test was conducted using a fixed 25-km route lasting approximately 30 minutes. Expert examiners assessed the participants’ driving skills and performance using assessment form measuring seven categories: car handling, observation/overview, signaling, positioning, speed adaption/risk, traffic flow/assessing gaps, and give way/traffic flow. Younger drivers reported significantly longer annual mileage (mean = 24,719 km) than older drivers (mean = 12,750 km). There were no significant group differences on self-reported number of accidents the last 3 years, driving frequency, or self-assessment scores. Independent sample t -test results show that compared to older drivers, the younger drivers scored significantly higher on 4 out of totally 32 category items in the assessment form. Two of them were in category total scores; car handling total score and speed adaption/risk total score , the other two were subcategory scores; use of controls and following traffic flow . The results indicate that aging itself and/or potential negative age-related decline in certain functions important for safe driving do effect driving performance, but less than expected and commonly assumed. One plausible explanation is that older drivers use compensatory actions related to factors like maturity and a behavioral adaptation to overcome difficulties in driving.